Copper Speciation in Soil: Time Evolution and Effect of Clay Amendment - Montenegro, Andrea Constanza (2015)
Copper bioavailability, specially to plants, is strongly dependent on its chemical form, as for most metals. Copper-contaminated soil can be treated in situ by the addition of minerals such as Na-bentonite, which mixed with surface soil, can transform this pollutant to non-bioavailable forms. In this work, shelter experiments were conducted to study the time evolution of Cu speciation, in pristine soil as well as in amended one. A selective sequential extraction method was employed to determine the metal speciation in the samples. The results show that the major metal fraction is the organic matter-bound one, whereas the exchangeable fraction is very low, even the first day after Cu addition. The time evolution shows a slow decrease of the organic-bound Cu and a corresponding increase of the most stable mineral fractions. With the addition of Na-bentonite to copper-contaminated soil, the most stable mineral fractions increase whereas the organic-bound one decreases, showing essentially similar time dependence of the several metal fractions. Sodium bentonite could be effectively used for remediation of soils polluted with Cu.